Exploring tabooed food among Dayaknese of Ngaju Women in Central Kalimantan Province, Indonesia - Suyitno; Suwarni, Linda; Asmarawanti; Sadli, Mohamad; Sera, Agnescia Clarissa (YCAB Publisher & IAKMI SULTRA, 2023)
Background: Dayak Ngaju is a sub-ethnic group of the Dayak tribe in Central Kalimantan, Indonesia. This group practices cultural practices as an identity, including the food taboo. Objective: This study aimed to explore the food taboo practices among women of Ngaju Dayaknese living in Central Kalimantan Province. Methods: A qualitative descriptive study was employed. A total of 12 informants were included, consisting of three pregnant women and two breastfeeding women as the main informants, five relatives of each woman, a midwife, and an ethnic leader. The in-depth interview was done in the study of Kartamulya Village, Sukamara District, Central Kalimantan Province. Content analysis was used for data analysis. Results: All the women were of reproductive age. Types of foods and dishes that are categorized as taboo include unripe pineapple, durian, chempedak, jackfruit; gourami (kalui), catfish/lele, puffer fish/buntal, wallago/tapah, snakehead fish/kerandang, marble goby/bakut/betutu, forest snakehead fish/jujung, shark catfish/patin; luffa gourd/gambas/oyong, bamboo shoots, stinky beans/jengkol; and soda. The food taboo for breastfeeding mothers was not described in detail. Conclusion: There was no reason to accept the scientific aspects of avoiding those foods rationally. Restricting the consumption of food during pregnancy and breastfeeding might have the risk of being anemic. Further study can include the anemia assessment to examine the impact of food taboo practices and anemia. Stakeholders at the village level can collaborate to decrease the negative health impact of food taboo practices on pregnant and breastfeeding mothers.